Evaluation of efficacy and biocompatibility of a new absorbable synthetic substitute as a dural onlay graft in a large animal model. (1st September 2016) - Deng, Kunxue; Ye, Xun; Yang, Yaya; Liu, Man; Ayyad, Ali; Zhao, Yuanli; Yuan, Yuyu; Zhao, Jizong; Xu, Tao
Abstract : Background: Numerous dura substitutes are commercially available, but no absorbable synthetic dura repair product has been used for both onlay and suture applications. Objective: The safety and effectiveness of a new absorbable synthetic substitute composed of Poly-L-lactide microfibers as onlay dural graft were evaluated. Methods: Physical properties and performance of the microfibrous synthetic dural substitute implanted as an onlay or suturable grafts were compared with these commercial products, including CODMAN ETHISORB™ Dura Patch and DuraGen™ Dural Graft Matrix, in a canine duraplasty model. The cerebrospinal fluid (CSF) leakage, macroscopic and microscopic observation at 30 and 90 days after implantation were investigated. Results: The absorbable synthetic dural substitute exhibited good wettability and conformability. When implanted as an onlay graft, it can prevent CSF leakage and integrate with the surrounding tissue to repair dural defects, indicating its good efficacy and biocompatibility as an onlay graft. Conclusion: Based on the excellent physical properties and performances mentioned above, the new absorbable synthetic substitute can be applied as a dural graft for both onlay and suturable applications.